Farmer Activities In Mekar Jaya Village As An Idea In The Creation Of Painting - Raharja, I Gusti Nyoman; Karja, I Wayan; Ruta, I Made (PROGRAM STUDI SENI MURNI ISI DENPASAR, 2024)
This Independent project study report raises the theme of farmer activities as an idea for creating paintings. Starting from personal experience who was born and raised in a farming family. By combining certain techniques, materials and references to achieve the desired goals and meaning. The problem faced is how to translate the visuals of farmers' activities into painting to support ideas so that the work looks attractive. The aims and benefits are to provide a reflection of farmers who carry out activities in the fields. To answer what is the aim of this work, the creation method involves exploration, experimentation, preparation and formation. By compiling elements of fine art through the stages of exploration, experimentation, preparation, and formation stages and combining them with ideas, 6 works were created entitled